2000
DOI: 10.1103/physrevb.61.r5137
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Stokes Raman spectra of single-walled carbon nanotubes

Abstract: An analysis of the Stokes and anti-Stokes resonant Raman spectra of single-walled carbon nanotubes ͑SWNT's͒ using different laser energies in the range 1.49рE laser р2.19 eV shows major differences in the tangential band spectra for the Stokes and anti-Stokes processes for selected E laser values. These differences arise from the differences in the one-dimensional density of electronic states for metallic and semiconducting nanotubes. This observation allows selection of E laser to excite only semiconducting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
109
1
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(122 citation statements)
references
References 6 publications
11
109
1
1
Order By: Relevance
“…As such, the broad G − peak was used as an indicator of the presence of metallic nanotubes for many years until further refinements were made (see Section VII). In another work by Brown et al, 82 it was shown that anti-Stokes and Stokes Raman spectra taken at the same excitation wavelengths demonstrated very different line shapes in their respective G-bands, one corresponding to metallic species and the other to semiconducting species.…”
Section: B Resonant Raman Scatteringmentioning
confidence: 99%
“…As such, the broad G − peak was used as an indicator of the presence of metallic nanotubes for many years until further refinements were made (see Section VII). In another work by Brown et al, 82 it was shown that anti-Stokes and Stokes Raman spectra taken at the same excitation wavelengths demonstrated very different line shapes in their respective G-bands, one corresponding to metallic species and the other to semiconducting species.…”
Section: B Resonant Raman Scatteringmentioning
confidence: 99%
“…Raman spectroscopy is a popular, non-destructive tool for structural characterisation of carbons [3][4][5][6][7][8][9][10][11][12]. It is traditionally carried out at the commonly available wavelengths in the blue-green spectral region (488-514.5 nm), but multi-wavelength Raman (MW Raman) studies are becoming increasingly used.…”
Section: Introductionmentioning
confidence: 99%
“…1 b), the observed lineshapes in the Stokes and Anti-Stokes spectra are markedly different. Such differences have been reported earlier in AD-SWNTs for incident laser energies ≤1.92 eV [9]. These studies have shown that significant additional Raman scattering intensity in the region of 1500-1550 cm -1…”
mentioning
confidence: 70%